حديث فاطمة في الذكر: دراسة تحليلية: The Hadith of Fatima in the Remembrance: An Analytical Study - Alenezi , Iqbal Ali Abdullah (Online Journal of Research in Islamic Studies, 2022)
The research studies and analyzes the hadith narrated by Ali bin Abi Talib, may God be pleased with him, in the remembrance of God before bedtime, a hadith found in the book of Sahih Al-Bukhari and Muslim, and made his title the hadith of Fatima in the remembrance, because it is related to her story, may God be pleased with her, and the research aims to collect the methods and words of the hadith and good formulation of the most important issues it contained. With the study of the difference that occurred in the narrations, and an attempt to harmonize them, and analyze the words of the hadith, and present some of its issues, by looking at the explanations of scholars on the hadith, and balancing between the sayings. The research concluded that some of the hadith narrations that Abu Hurairah said, may God be pleased with him, confirmed the mention of glorification without mentioning the story of Fatima, may God be pleased with her.